Identifying key performance indicators for Manufacturing Industries Bumiputera Entrepreneurs (MIBE) in East Coast Malaysia - Saiful Bahri, Mohamed; Abdul Aziz, Abdullah (2019)
The Manufacturing Industries in Malaysia were the fastest-growth industry over the past few years. In doing so, involvement of Bumiputera Entrepreneurs in this area was competitive. After the support gave from the government to the entrepreneur, the government still doesn’t have any apparatus for analyzing Manufacturing Industries Bumiputera Entrepreneur (MIBE) performance. The development of the MIBE performance index will give the government, agencies and other stakeholders a clear picture of the success achieved so far, the efficacy of strategies used, failures if any, areas that needed to be polished, so as to achieve optimum utilization of resources towards the entrepreneurship development. Similarly, the government will be able to use this performance index in order to have a stand on whether to continue with the support or make necessary adjustments. However, there are limited published studies on the evaluation of the sustainability performance of the MIBE sector. Thus, this paper aims to formulate a list of key performance index (KPI) for the MIBE. First, a literature study on the Bumiputera Entrepreneur development carried out. This study continued with study of KPI from various industries. Finally, a set of KPI which can be used for measuring performance index in MIBE was identified. These KPI was used to design a question which will be distributed to some agencies to strengthen the list of performance index .